PENGARUH RELIGIUSITAS DAN PENGETAHUAN AKUNTANSI SYARIAH TERHADAP MINAT MAHASISWA AKUNTANSI SYARIAH BEKARIR DILEMBAGA KEUANGAN SYARIAH - Maulana Yusuf; Lidya Anggraeni; Rika, Rika Amelia (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to determine the effect of religiosity and knowledge of Islamic accounting on a career in Islamic financial institutions. The research used quantitative methods, namely the method of multiple linier regression analysis with a sample of 78 respondent, by using purposive sampling. As for the provisions, students from the Islamic accounting study program who have passed the Islamic accounting course and have passed the Islamic financial institutions course. The results of this study are that religiosity has no significant effect on the interest of Islamic accounting students to have a career in Islamic financial institutions, while Islamic accounting knowledge has a significant effect on students desires for a career in Islamic financial institutions. Keywords: Religiosity, sharia Accounting Knowledge, career interest of Islamic accounting students in a career in Islamic financial institutions.